Psychometric properties and measurement invariance of the sociocultural adjustment scale among international students in Malaysia - En, Cui; Rosnon, Mohd Roslan; Zaremohzzabieh, Zeinab; Abd. Razak, Muhammad Afiq; Amin, Samir Muhazzab (Institute of Advanced Science Extension (IASE), 2024)
The sociocultural adaptation scale is a tool commonly used to assess how international students adjust to new cultures. Although it has been shown to be useful, there's little proof that it works well for students in non-Western countries. Our study aimed to create and test a version of this tool for international students in Malaysia, with 428 participants. We looked at whether the tool worked the same way for people of different genders, ages, and academic majors. At first, our results showed that the tool was not a perfect fit, but after careful adjustments, including removing items that did not fit well and improving how items were linked, we significantly improved how well the tool worked. The updated tool effectively measures how well international students adapt to new cultures. Moreover, our study found that the tool worked consistently across different demographic groups, offering new insights into how gender, age, and academic major affect students' sociocultural adaptation. These findings make the tool more useful in various settings and help us better understand the complex factors that influence how international students adjust to living in multicultural environments.